Preparation method of perfluorinated sulfonic acid resin for hydrogen-oxygen fuel cell
The perfluorosulfonic acid resin for hydroxide fuel cells was prepared by emulsion polymerization, which solved the problems of improving space and safety hazards of conductivity and oxygen permeability in the prior art, and realized high-performance hydroxide fuel cell membrane material, with excellent physical and mechanical properties and ion exchangeability.
Patent Information
- Application Number
- CN202411530411.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing perfluorosulfonic acid resin film for hydroxide fuel cells has room for improvement in improving conductivity and oxygen permeability. In addition, traditional polymerization methods have safety hazards and unstable product quality, making it difficult to take into account both physical and mechanical properties and ion exchange equivalent. and oxygen permeability.
Perfluorosulfonic acid resin is prepared by emulsion polymerization method. By adding deoxygenated water, monomer, emulsifier and auxilizer to the polymerization kettle, the temperature and pressure of the polymerization kettle are controlled, TFE gas is introduced for copolymerization, and copolymerization is passed through a coagulant and acid The solution was converted to finally obtain a hydrogen perfluorosulfonic acid resin with excellent properties.
Perfluorosulfonic acid resin with high conductivity and oxygen permeability has excellent physical and mechanical properties, significantly improved tensile strength and elongation at break. It is suitable for proton exchange membranes in high-efficiency fuel cells, with reduced EW value and oxygen Increase through constant.
Smart Images

Figure CN119264316A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, in particular to a method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells. Background Art
[0002] Perfluorosulfonic acid resin membranes, with their excellent chemical stability, mechanical properties, and electrochemical properties, have promoted the development of the global battery industry towards low energy consumption and pollution-free. Hydrogen-oxygen fuel cells have the advantages of high energy conversion rate, zero emissions, and no noise, and have therefore become energy conversion devices that are the focus of research and development in countries around the world. The key component of hydrogen-oxygen fuel cells, the ion exchange membrane, is mostly based on perfluorosulfonic acid ion membranes. In hydrogen-oxygen fuel cells, hydrogen at the anode is electrolyzed to generate protons, which pass through the perfluorosulfonic acid proton membrane and combine with oxygen at the cathode, thereby converting chemical energy into electrical energy. Its conversion efficiency is largely related to the conductivity and oxygen permeability of the proton membrane.
[0003] CN101220120A discloses a method for synthesizing a fluororesin with sulfonyl fluoride and ether end groups, which is mainly formed by ternary copolymerization of tetrafluoroethylene A, sulfonyl fluoride end group enol ether monomer B, and alkyl ether end group enol ether monomer C, wherein the first two monomers are the main components of polymerization, and the alkyl ether end group enol ether monomer C is a functional monomer with a molar ratio of 0.01% to 5%. The prepared perfluoro ion exchange membrane has high conductivity and is suitable for use in fuel cells or chlor-alkali electrolytic cells. The reported dispersed polymerization test product using persulfate as an initiator has an exchange capacity IEC value of up to 0.96mmol / g, and the corresponding ion exchange equivalent EW is 1041g / mol. However, the copolymerization raw material alkyl ether end group enol ether monomer C has an alkyl group as the long side chain end group and does not contain a sulfonyl fluoride functional group. The conductivity of the resin prepared after introduction still has room for improvement, and the product has poor oxygen permeability, which affects its application in the field of hydrogen fuel cells.
[0004] CN114085310A discloses a bulk polymerization method for preparing a perfluorosulfonic acid resin, which is mainly prepared by copolymerizing tetrafluoroethylene A, a monomer B containing a sulfonyl fluoride end group, and a monomer C containing a sulfonyl fluoride end group, at a polymerization temperature of 30-100°C and a pressure of 0.5-5MPa, to finally obtain a sulfonyl fluoride type perfluorosulfonic acid resin. The structural formula of monomer C is: Monomer C contains dioxole. The resin prepared by introducing monomer C has high oxygen permeability, and the oxygen permeability constant can reach up to 6.6cm3 / (m·24h·0.1MPa). It is usually used for proton exchange membranes in fuel cells. However, bulk polymerization has a large relative heat release, high system viscosity, and serious local overheating. If it is not properly controlled, it will cause a wide distribution of polymer relative molecular weight, affecting product quality, or even cause explosion and polymerization, which is a big safety hazard.
[0005] At present, the perfluorosulfonic acid resin membrane used in hydrogen and oxygen fuel cells must meet the following requirements: good physical and mechanical properties, low ion exchange equivalent, and high membrane oxygen permeability constant. Existing patent reports mostly focus on the selection of the third functional monomer, optimizing the corresponding performance by changing some side chain structures in the polymer, but often cannot take both into account. Therefore, it is urgent to find a new preparation method that can improve the comprehensive performance of perfluorosulfonic acid resin products.
[0006] In view of this, the present invention is proposed to prepare a perfluorosulfonic acid resin with high conductivity and oxygen permeability for application in high-efficiency fuel cells. Summary of the invention
[0007] The present invention provides a method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell. The resin is prepared by emulsion polymerization. Compared with bulk polymerization, solution polymerization and suspension polymerization, emulsion polymerization is suitable for producing high molecular weight polymers. Water is used as a medium, and the reaction safety performance is high and the reaction rate is fast, which is suitable for industrial production. The production steps are as follows: A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell, the operating steps of which are as follows: S1: According to the weight ratio, 2000-2200 parts of deoxygenated high-purity water, 150-250 parts of a mixture of monomer A and monomer B, 10-20 parts of an emulsifier D and an auxiliary emulsifier are added to a polymerization kettle, stirring is started, the stirring speed is 100-300 rpm, the polymerization kettle is heated to 60-100° C., tetrafluoroethylene gas of monomer C is introduced until the pressure of the polymerization kettle is 800-2000 kPa, and 0.01-0.5 parts of an initiator E are added to initiate a copolymerization reaction; S2: After the polymerization starts, TFE gas is introduced to maintain the pressure of the polymerization kettle at 800-2000 kPa. When the TFE consumption reaches 150-250 parts, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 50-80 parts of coagulant F to the obtained emulsion for coagulation and washing to obtain sulfonyl fluoride type perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride type perfluorosulfonic acid resin into a film with a thickness of 100 μm, cut the resin film into small particles, soak it in 1000-1200 parts of 48% potassium hydroxide solution, reflux at 80-110°C for 24 hours to obtain potassium type perfluorosulfonic acid resin, wash it with pure water until neutral, soak it in 1000-1200 parts of 68% nitric acid solution, reflux at 80-110°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product hydrogen type perfluorosulfonic acid resin.
[0008] The monomer A is a sulfonyl fluoride terminal olefin ether, and the structural formula is CF2=CFO[CF2CF(CF3)O]a[CF2CF2]bSO2F, wherein a=an integer of 0 to 1, and b=an integer of 1 to 2. Preferably a=b=1, and perfluorosulfonyl vinyl ether (PSVE) is preferred.
[0009] The monomer B is a dioxolane ether containing multiple sulfonyl fluoride end groups, and the structural formula is: Wherein c=an integer of 0-2, d=an integer of 0-2, preferably c=d=1.
[0010] In the step S1, the molar ratio of the mixture of monomer A and monomer B:monomer C tetrafluoroethylene is 2:1-9:1, wherein the molar ratio of monomer A:monomer B is 15:1-30:1.
[0011] In the step S2, the molar ratio of the mixture of monomer A and monomer B:monomer C tetrafluoroethylene is 0.5:1-2:1, wherein the molar ratio of monomer A:monomer B is 15:1-30:1.
[0012] The emulsifier D is selected from perfluoropolyether surfactants, and has the structural formula R1-[CF(CF3)-CF2-O]e-CF(CF3)R2, wherein R1 is selected from fluorine or other halogen groups, R2 is selected from C1~C10 perfluoroacyl fluoride or C3~C12-hydroxyperfluoroalkyl, and e=an integer of 4~10.
[0013] The initiator E is selected from one or more mixtures of peroxy alcohols, peroxy esters, peroxy acids, peroxy acyl, persulfates, perchlorates and the like.
[0014] The coagulant F is selected from a high-concentration inorganic acid, selected from one of nitric acid, sulfuric acid, hydrochloric acid and the like.
[0015] The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: Mix 0.5-2 parts of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) and 0.002-0.02 parts of 2-aminoadipate lithium by weight; add 200-300 parts of ethanol as a solvent; under the catalytic condition of 2-4 parts of sodium ethoxide, the reaction temperature is controlled at 65-75 degrees Celsius and the reaction time is 50-100 minutes; Step 2: further add 25-40 parts of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) to the mixture, react the resulting mixture at a temperature of 65-75° C. for 60-80 minutes, remove ethanol by distillation, and obtain the desired co-emulsifier.
[0016] The amount of the co-emulsifier added is 1-4% by mass of the emulsifier D.
[0017] Reaction mechanism: 1. Amine-epoxy ring-opening reaction: Epoxycyclohexyl-cage polysilsesquioxane undergoes an amine-epoxy ring-opening reaction with 2-amino lithium adipate. In this reaction, the amine group (-NH2) attacks the carbon atom in the epoxy group, resulting in the ring opening of the epoxy group and the formation of a new hydroxyl group and a secondary amine group.
[0018] 2. Amine-epoxy ring-opening reaction again: The newly formed secondary amine group in the ring-opening product continues to undergo an amine-epoxy ring-opening reaction with the epoxy group in diethyl 12-mercaptododecyl phosphate. Similarly, the secondary amine group attacks the epoxy group, resulting in further ring opening and the formation of new hydroxyl and tertiary amine groups.
[0019] Technical effect: Compared with traditional methods, this method has the following advantages: 1. Improve emulsification efficiency: During the polymerization process of perfluorosulfonic acid resin, the phosphate emulsifier containing polysilsesquioxane and lithium adipate works together with the perfluoropolyether emulsifier to more effectively stabilize the emulsion, reduce surface tension and improve emulsification efficiency.
[0020] 2. Enhance product performance: The addition of co-emulsifiers can improve the uniformity and stability of the final product and help obtain a finer particle size distribution, which may improve the performance of perfluorosulfonic acid resins, such as enhancing their mechanical strength, chemical resistance and heat resistance.
[0021] 3. Controlling the polymerization rate: The presence of co-emulsifiers may affect the rate of the polymerization reaction. By controlling the concentration and type of the emulsifier, the polymerization rate can be adjusted to a certain extent, thereby achieving better control over the polymerization process.
[0022] 4. The perfluorosulfonic acid resin product prepared by the present invention has excellent physical and mechanical properties, with a tensile strength of ≥27MPa and an elongation at break of ≥350%.
[0023] 5. The perfluorosulfonic acid resin product prepared by the present invention has excellent ion exchange and oxygen permeability, and is suitable for the preparation of proton exchange membranes in fuel cells, with an EW value of ≤940 g / mol and an oxygen permeability constant of ≥7.0 cm3 / (m·24h·0.1MPa). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The ATR infrared spectrum of the fluorinated perfluorosulfonic acid resin during the preparation process of Example 1; Figure 2 This is the ATR infrared spectrum of the hydrogen-type perfluorosulfonic acid resin prepared in Example 1. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0026] Example 1 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 4.8 kg of PSVE, 0.2 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.5 kg of F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF, and 0.005 kg of co-emulsifier were added to an 80 L polymerization kettle, stirring was started at a stirring speed of 300 rpm, the polymerization kettle was heated to 100° C., TFE gas was introduced until the pressure of the polymerization kettle reached 2000 kPa, and 0.0025 kg of potassium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: 0.5 g of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) and 0.002 g of 2-aminoadipate lithium were stirred and mixed; 200 g of ethanol was added as a solvent; under the catalytic condition of 2 g of sodium ethoxide, the reaction temperature was controlled at 65 degrees Celsius and the reaction time was 50 minutes; Step 2: 25 g of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) was further added to the mixture, and the resulting mixture was reacted at 65° C. for 60 minutes. Ethanol was removed by distillation to obtain the desired co-emulsifier.
[0027] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 2000 kPa. When the TFE consumption reaches 5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.8kg of 50% sulfuric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 30kg of 48% potassium hydroxide solution, reflux and transform it at 100°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water to neutrality, soak it in 30kg of 68% nitric acid solution, reflux and transform it at 100°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0028] Example 2 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 4.7 kg of PSVE, 0.3 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.4 kg of F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF, and 0.008 kg of co-emulsifier were added to a 80 L polymerization kettle, stirring was started at a stirring speed of 300 rpm, the polymerization kettle was heated to 80° C. TFE gas was introduced until the pressure of the polymerization kettle reached 1800 kPa, and 0.0025 kg of ammonium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: 1 g of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) and 0.008 g of lithium 2-aminoadipate were stirred and mixed; 250 g of ethanol was added as a solvent; under the catalytic condition of 3 g of sodium ethoxide, the reaction temperature was controlled at 70 degrees Celsius and the reaction time was 75 minutes; Step 2: 30 g of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) was further added to the mixture, and the resulting mixture was reacted at 70° C. for 70 minutes. The ethanol was removed by distillation to obtain the desired co-emulsifier.
[0029] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 1800 kPa. When the TFE consumption reaches 5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: The obtained emulsion is added with 1.5 kg of 68% nitric acid solution for condensation and washing to obtain sulfonyl fluoride type perfluorosulfonic acid resin. At an operating temperature of 240°C, the sulfonyl fluoride type perfluorosulfonic acid resin is pressed into a film with a thickness of 100 μm using a flat vulcanizer. After the resin film is cut into small particles, it is immersed in 25 kg of 48% potassium hydroxide solution, refluxed at 80°C for 24 hours to obtain potassium type perfluorosulfonic acid resin, washed with pure water until neutral, immersed in 25 kg of 68% nitric acid solution, refluxed at 80°C for 24 hours, and the resin is washed until neutral, and dried at 100°C for 24 hours to obtain the final product hydrogen type perfluorosulfonic acid resin.
[0030] Example 3 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 6.13 kg of PSVE, 0.27 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.5 kg of F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF, and 0.015 kg of co-emulsifier were added to an 80 L polymerization kettle, stirring was started at a speed of 200 rpm, the polymerization kettle was heated to 100° C., TFE gas was introduced until the pressure of the polymerization kettle reached 2000 kPa, and 0.0025 kg of potassium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: 1.5 g of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) and 0.01 g of 2-aminoadipate lithium were stirred and mixed; 250 g of ethanol was added as a solvent; under the catalytic condition of 3 g of sodium ethoxide, the reaction temperature was controlled at 70 degrees Celsius and the reaction time was 75 minutes; Step 2: 35 g of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) was further added to the mixture, and the resulting mixture was reacted at 70° C. for 70 minutes. Ethanol was removed by distillation to obtain the desired co-emulsifier.
[0031] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 2000 kPa. When the TFE consumption reaches 4.5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.8kg of 50% sulfuric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 30kg of 48% potassium hydroxide solution, reflux and transform it at 100°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water to neutrality, soak it in 30kg of 68% nitric acid solution, reflux and transform it at 100°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0032] Example 4 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 6.17 kg of PSVE, 0.23 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.4 kg of emulsifier D (F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF), and 0.016 kg of co-emulsifier were added to a 80 L polymerization kettle, stirring was started at a stirring speed of 200 rpm, the polymerization kettle was heated to 80° C. TFE gas was introduced until the pressure of the polymerization kettle reached 1800 kPa, and 0.0025 kg of ammonium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: Mix 0.5-2 parts of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) and 0.002-0.02 parts of 2-aminoadipate lithium, add 200-300 parts of ethanol as a solvent, and control the reaction temperature at 65-75 degrees Celsius under the catalytic condition of 2-4 parts of sodium ethoxide for 50-100 minutes. Step 2: further add 25-40 parts of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) to the mixture, react the resulting mixture at a temperature of 65-75° C. for 60-80 minutes, remove ethanol by distillation, and obtain the desired co-emulsifier.
[0033] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 1800 kPa. When the TFE consumption reaches 4.5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.5kg of 68% nitric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 25kg of 48% potassium hydroxide solution and reflux it at 80°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water until neutral, soak it in 25kg of 68% nitric acid solution, reflux it at 80°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0034] Comparative Example 1 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 4.8 kg of PSVE, 0.2 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, and 0.5 kg of emulsifier D (F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF) were added to an 80 L polymerization kettle, stirring was started at a speed of 300 rpm, the polymerization kettle was heated to 100° C., TFE gas was introduced until the pressure of the polymerization kettle reached 2000 kPa, and 0.0025 kg of potassium persulfate was added to initiate copolymerization; S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 2000 kPa. When the TFE consumption reaches 5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.8kg of 50% sulfuric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 30kg of 48% potassium hydroxide solution, reflux and transform it at 100°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water to neutrality, soak it in 30kg of 68% nitric acid solution, reflux and transform it at 100°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0035] Comparative Example 2 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 4.8 kg of PSVE, 0.2 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.5 kg of F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF, and 0.005 kg of co-emulsifier were added to an 80 L polymerization kettle, stirring was started at a speed of 300 rpm, the polymerization kettle was heated to 100° C., TFE gas was introduced until the pressure of the polymerization kettle reached 2000 kPa, and 0.0025 kg of potassium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: 0.002 g of lithium 2-aminoadipate was stirred into 200 g of ethanol; under the catalytic condition of 2 g of sodium ethoxide, the reaction temperature was controlled at 65 degrees Celsius and the reaction time was 50 minutes; Step 2: 25 g of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) was further added to the mixture, and the resulting mixture was reacted at 65° C. for 60 minutes. Ethanol was removed by distillation to obtain the desired co-emulsifier.
[0036] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 2000 kPa. When the TFE consumption reaches 5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.8kg of 50% sulfuric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 30kg of 48% potassium hydroxide solution, reflux and transform it at 100°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water to neutrality, soak it in 30kg of 68% nitric acid solution, reflux and transform it at 100°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0037] Comparative Example 3 A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell comprises the following steps: S1: 50 kg of deoxygenated high-purity water, 4.8 kg of PSVE, 0.2 kg of dioxolan ether containing multiple sulfonyl fluoride end groups, 0.5 kg of F-[CF(CF3)-CF2-O]4-CF(CF3)CF2COF, and 0.005 kg of co-emulsifier were added to an 80 L polymerization kettle, stirring was started at a speed of 300 rpm, the polymerization kettle was heated to 100° C., TFE gas was introduced until the pressure of the polymerization kettle reached 2000 kPa, and 0.0025 kg of potassium persulfate was added to initiate copolymerization; The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: Add 0.5 g of epoxycyclohexyl-cage polysilsesquioxane (CAS No. 187333-74-0) to 200 g of ethanol; under the catalytic condition of 2 g of sodium ethoxide, the reaction temperature is controlled at 65 degrees Celsius and the reaction time is 50 minutes; Step 2: 25 g of diethyl 12-mercaptododecyl phosphate (CAS No. 1049677-30-6) was further added to the mixture, and the resulting mixture was reacted at 65° C. for 60 minutes. Ethanol was removed by distillation to obtain the desired co-emulsifier.
[0038] S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 2000 kPa. When the TFE consumption reaches 5 kg, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 1.8kg of 50% sulfuric acid solution to the obtained emulsion for condensation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin. At an operating temperature of 240°C, use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100μm. After cutting the resin film into small particles, soak it in 30kg of 48% potassium hydroxide solution, reflux and transform it at 100°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin. After washing with pure water to neutrality, soak it in 30kg of 68% nitric acid solution, reflux and transform it at 100°C for 24 hours, wash the resin to neutrality, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
[0039] The main test items and methods are as follows: Ion exchange equivalent EW value: The test method refers to GB / T 20042.3-2022, and the common unit is g / mol. Dry the resin sample in a vacuum oven at 80°C and 50 mmHg vacuum for 8 hours, cool it in a sealed container, and quickly weigh the mass of the dry film m using an analytical balance; place it in a sealed reagent bottle filled with saturated NaCl solution and stir it for 24 hours; then, titrate it to neutrality with a NaOH standard solution using an automatic potentiometric titrator, and record the volume of the consumed NaOH solution VNaOH. The EW value (unit: g / mol) is calculated as follows: EW=m / (CNaOH*VNaOH) Oxygen permeation constant: The test method refers to GB / T 19789-2021, and the common unit is cm3 / (m·24h·0.1MPa). The test sample is clamped in the permeation chamber to form a closed barrier layer between the two chambers; the B chamber is slowly purged with nitrogen carrier gas, and oxygen is injected into the A chamber. The total pressure in each chamber is equal (atmospheric pressure), but because the partial pressure of oxygen in the A chamber is higher, oxygen passes through the sample into the B chamber, and enters the coulometer with the nitrogen carrier gas to undergo a chemical reaction and generate a voltage, which is proportional to the amount of oxygen passing through the coulometer per unit time.
[0040] Test items unit Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile Strength MPa 30 31 27 27 22 25 24 Elongation at break % 368 358 360 349 322 344 346 EW value g / mol 935 919 918 928 901 914 910 Oxygen permeability constant cm3 / (m·24h·0.1MPa) 7.3 8.2 8.0 7.8 6.0 7.0 6.9 It can be seen from the above specific embodiments that the perfluorosulfonic acid resin product prepared by the method of the present invention has excellent physical and mechanical properties, excellent ion exchangeability and oxygen permeability, and is suitable for the preparation of proton exchange membranes in fuel cells.
[0041] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a perfluorosulfonic acid resin for a hydrogen-oxygen fuel cell, the operating steps of which are: S1: According to the weight ratio, 2000-2200 parts of deoxygenated high-purity water, 150-250 parts of a mixture of monomer A and monomer B, 10-20 parts of an emulsifier D and an auxiliary emulsifier are added to a polymerization kettle, stirring is started, the stirring speed is 100-300 rpm, the polymerization kettle is heated to 60-100° C., tetrafluoroethylene gas of monomer C is introduced until the pressure of the polymerization kettle is 800-2000 kPa, and 0.01-0.5 parts of an initiator E are added to initiate a copolymerization reaction; S2: After the polymerization starts, TFE gas is introduced to maintain the polymerization kettle pressure at 800-2000 kPa. When the TFE consumption reaches 150-250 parts, the copolymerization reaction is terminated and the polymerization kettle is depressurized and discharged; S3: Add 50-80 parts of coagulant F to the obtained emulsion for coagulation and washing to obtain sulfonyl fluoride perfluorosulfonic acid resin; use a flat vulcanizer to press the sulfonyl fluoride perfluorosulfonic acid resin into a film with a thickness of 100 μm at an operating temperature of 240°C; cut the resin film into small particles, immerse it in 1000-1200 parts of 48% potassium hydroxide solution, reflux and transform it at 80-110°C for 24 hours to obtain potassium-type perfluorosulfonic acid resin; wash it with pure water until it is neutral; immerse it in 1000-1200 parts of 68% nitric acid solution, reflux and transform it at 80-110°C for 24 hours, wash the resin until it is neutral, and dry it at 100°C for 24 hours to obtain the final product, hydrogen-type perfluorosulfonic acid resin.
2. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The monomer A is a sulfonyl fluoride terminal olefin ether, and has the structural formula CF2=CFO[CF2CF(CF3)O]a[CF2CF2]bSO2F, wherein a=an integer of 0-1, and b=an integer of 1-2.
3. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The monomer B is a dioxolane ether containing multiple sulfonyl fluoride end groups, and the structural formula is: Wherein c=an integer from 0 to 2, and d=an integer from 0 to 2.
4. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: In the step S1, the molar ratio of the mixture of monomer A and monomer B:monomer C tetrafluoroethylene is 2:1-9:1, wherein the molar ratio of monomer A:monomer B is 15:1-30:
1.
5. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The emulsifier D is selected from perfluoropolyether surfactants, and has the structural formula R1-[CF(CF3)-CF2-O]e-CF(CF3)R2, wherein R1 is selected from fluorine or other halogen groups, R2 is selected from C1~C10 perfluoroacyl fluoride or C3~C12-hydroxyperfluoroalkyl, and e=an integer of 4~10.
6. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The initiator E is selected from one or more mixtures of peroxy alcohols, peroxy esters, peroxy acids, peroxy acyl, persulfates, perchlorates and the like.
7. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The coagulant F is selected from a high-concentration inorganic acid, selected from one of nitric acid, sulfuric acid, hydrochloric acid and the like.
8. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The preparation method of the auxiliary emulsifier comprises the following steps: Step 1: by weight, 0.5-2 parts of epoxycyclohexyl-cage polysilsesquioxane and 0.002-0.02 parts of 2-amino lithium adipate are stirred and mixed; 200-300 parts of ethanol are added as a solvent; under the catalytic condition of 2-4 parts of sodium ethoxide, the reaction temperature is controlled at 65-75 degrees Celsius, and the reaction time is 50-100 minutes; Step 2: further add 25-40 parts of diethyl 12-mercaptododecyl phosphate to the mixture, react the resulting mixture at a temperature of 65-75° C. for 60-80 minutes, remove ethanol by distillation, and obtain the desired co-emulsifier.
9. The method for preparing a perfluorosulfonic acid resin for hydrogen and oxygen fuel cells according to claim 1, characterized in that: The amount of the co-emulsifier added is 1-4% by mass of the emulsifier D.
Citation Information
Patent Citations
Machine for shafting and finishing leather loops
CA50100A
Fluor resin with sulfuryl fluoride and aether terminal group lateral group, synthesizing method and application thereof
CN101220120A